Ответы и объяснения

2012-02-13T10:08:07+04:00
2012-02-13T10:39:26+04:00

Выражение: 1.3*(x-0.6)=1.8*x

Ответ: -0.5*x-0.78=0

Решаем по действиям:
1) 1.3*(x-0.6)=1.3*x-0.78
  1.3*(x-0.6)=1.3*x-1.3*0.6
  1.1) 1.3*0.6=0.78
      X1.3
       _0_._6_ _
       78
      0_0_ _ _
      0.78
2) 1.3*x-1.8*x=-0.5*x

Решаем по шагам:
1) 1.3*x-0.78-1.8*x=0
  1.1) 1.3*(x-0.6)=1.3*x-0.78
      1.3*(x-0.6)=1.3*x-1.3*0.6
    1.1.1) 1.3*0.6=0.78
          X1.3
           _0_._6_ _
           78
          0_0_ _ _
          0.78
2) -0.5*x-0.78=0
  2.1) 1.3*x-1.8*x=-0.5*x